Lipid metabolism disorder promoting retinal structural and functional damage in ApoE −/− mice with age superposition - Rucui Yang; Shaolang Chen; Tsz Kin Ng; Jiajian Liang; Shaofen Huang; Minru Deng; Zhenggen Wu; Yaru Sun; Changzhen Fu; Chi Pui Pang; Qingping Liu; Mingzhi Zhang (Acta Neuropathologica Communications)
Abstract This study aimed to establish a model of abnormal lipid metabolism in Apolipoprotein E (ApoE) knockout mice by feeding them a high-fat diet (HFD) and to investigate the impact of this abnormal lipid metabolism on retinal blood perfusion, structure, and function, particularly the retinal ganglion cell (RGC). Both HFD and regular diet (RD) feeding were conducted in C57BL/6J mice and ApoE −/− mice. Lipid metabolism was assessed using hematoxylin-eosin (HE) staining, oil red staining, and blood lipid detection. Retinal microcirculation was evaluated through fundus fluorescein angiography. The expression levels of inflammatory cytokines were determined using quantitative reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay. Intraocular pressure, retinal structure, and RGCs were assessed using tonometer, optical coherence tomography, HE staining, and immunofluorescence staining. Retinal function was measured by electroretinogram. Hyperlipidemia was induced in ApoE −/− mice fed HFD. Retinal microcirculation was impaired in mice with abnormal lipid metabolism, while the expression of the inflammatory cytokine Tnf-α was significantly increased in atherosclerotic plaques, serum, and retina. Ultimately, compared with normal mice on a RD, ApoE −/− mice fed HFD exhibited no significant changes in intraocular pressure but demonstrated decreased RGC density and impaired retinal structure and function of the inner and outer layers of the retina. The abnormal lipid metabolism in ApoE −/− mice fed a HFD can exacerbate the disturbance of intraocular microcirculation and RGC loss caused by aging, as well as inflammation of the intraocular microenvironment and damage to retinal function.